2008
DOI: 10.1080/03601230802519579
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Diuron, Linuron and their main metabolites in undisturbed field lysimeters

Abstract: The increasing use of pesticides in Morocco raises the potential risk of groundwater contamination, notably in the Gharb area, which has a shallow groundwater table. Thus, the leaching of two phenyl-ureas, diuron and linuron and their metabolites through undisturbed soil columns was studied under outdoor conditions. The soil chosen is a loamy clay soil, representative of the Gharb agricultural area. After four irrigation events were applied from 31/03/2005 to 15/05/2005, leachates contained higher amounts of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
1
2
0
2
Order By: Relevance
“…Noteworthy, diuron is classified as a known carcinogenic compound (US-EPA, 1999). Owing to its stability in the environment (Dores et al, 2009), groundwater contamination by diuron has been reported as a significant environmental concern in Brazil (Ellmache et al, 2009). Similar findings have been reported in Dutch coastal waters (Lamoree et al, 2002) as well as in France (IFEN, 2002) and the United Kingdom (UK-EPA, 2002).…”
Section: Introductionsupporting
confidence: 55%
“…Noteworthy, diuron is classified as a known carcinogenic compound (US-EPA, 1999). Owing to its stability in the environment (Dores et al, 2009), groundwater contamination by diuron has been reported as a significant environmental concern in Brazil (Ellmache et al, 2009). Similar findings have been reported in Dutch coastal waters (Lamoree et al, 2002) as well as in France (IFEN, 2002) and the United Kingdom (UK-EPA, 2002).…”
Section: Introductionsupporting
confidence: 55%
“…Dores's research [8] showed that diuron was detected in concentration decreasing until 70 days after application in runoff water and soil, totalizing 13.9% during the whole sampling period. Because of its high persistence, groundwater contamination by diuron has become a serious problem [9]. In Dutch coastal waters a higher level of diuron than the permitted 430 ng L −1 was detected [10].…”
Section: Introductionmentioning
confidence: 99%
“…Sample pretreatment processes are crucial steps to achieve clean-up and effective enrichment of the target analytes before analysis. For solid samples, traditionally, Soxhlet and manual/mechanical shaking have been used for ureas extraction (Buszewski et al, 2006;Cydzik et al, 2007;El Imache et al, 2009;Ghanem et al, 2008;Mou et al, 2008;Scheyer et al, 2005;Tamayo et al, 2005a, b;Tamayo & Martin-Esteban, 2005). On the other hand, for aqueous samples the classical methodology is liquid-liquid extraction (Moros et al, 2005).…”
Section: Methodsmentioning
confidence: 99%